2020
DOI: 10.1136/bjophthalmol-2019-315746
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TIE2 as a susceptibility gene for neovascular age-related macular degeneration and polypoidal choroidal vasculopathy

Abstract: PurposeThe endothelial and cell-specific angiopoietin-Tie pathway plays an important regulatory role in angiogenesis. In this study, we investigated the associations of the TIE2 (tyrosine kinase, endothelial, TEK) gene with neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV), using haplotype-tagging single-nucleotide polymorphisms (SNPs) analysis.MethodsThis study involved totally 2343 subjects, including a Hong Kong Chinese cohort (214 nAMD patients, 236 PCV patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…21 A recent study revealed significant association between TIE2 gene in the endothelial and cell-specific angiopoietin-Tie pathway of angiogenesis with nAMD and PCV in multiple East Asian cohorts. 22 In a meta-analysis, 31 SNPs in 10 AMD-associated genes/ loci (ARMS2, HTRA1, CFH, C2, CFB, RDBP, SKIV2L, CETP, 8p21, and 4q12) were found to be significantly associated with PCV, whereas 12 SNPs at the ARMS2-HTRA1 locus showed significant differences between PCV and nAMD, with the stronger effect sizes for the latter. In another candidate gene analysis, 23 34 known AMD loci were studied in PCV among East Asians.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 A recent study revealed significant association between TIE2 gene in the endothelial and cell-specific angiopoietin-Tie pathway of angiogenesis with nAMD and PCV in multiple East Asian cohorts. 22 In a meta-analysis, 31 SNPs in 10 AMD-associated genes/ loci (ARMS2, HTRA1, CFH, C2, CFB, RDBP, SKIV2L, CETP, 8p21, and 4q12) were found to be significantly associated with PCV, whereas 12 SNPs at the ARMS2-HTRA1 locus showed significant differences between PCV and nAMD, with the stronger effect sizes for the latter. In another candidate gene analysis, 23 34 known AMD loci were studied in PCV among East Asians.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Candidate genes in the pathways other than complement have also been implicated in both nAMD and PCV, such as the angiogenesis pathway [eg, vascular endothelial growth factor ( VEGF ), placental growth factor (PGF),15 and ANGPT2 16], high-density lipoprotein (HDL) metabolic pathway [eg, cholesterol ester transfer protein ( CETP )17 and ABCG1 18], fatty acid biosynthesis pathway (eg, ELOVL4 19), the phagocytic pathway (eg, P2RX4 and P2RX7 20), and smoking-related inflammation gene (eg, FPR1 ) 21. A recent study revealed significant association between TIE2 gene in the endothelial and cell-specific angiopoietin-Tie pathway of angiogenesis with nAMD and PCV in multiple East Asian cohorts 22…”
Section: Updates On Risk Factors and Biomarkers For Pcv Developmentmentioning
confidence: 99%
“…Thus, ANGPT-TEK signaling has an essential role in developing the choroidal circulation system. In humans, polypoidal choroidal vasculopathy-associated variants are found in ANGPT2 [ 66 ] and TEK [ 67 ], and additional variants related to central serous chorioretinopathy are identified in PTPRB [ 68 ], which encodes phosphatase dephosphorylating TEK [ 69 ]. Further research about the roles of stromal cells and ANGPT-TEK signaling in choroidal development would contribute to a further understanding of ocular diseases.…”
Section: Neural Crest-derived Stromal Cellsmentioning
confidence: 99%
“…Fine-mapping a candidate gene can pinpoint the causal variant and SNP analysis and help identify rare disease-associated coding variants. For example, the placental growth factor ( PGF ), angiopoietin 2 ( ANGPT2 ), and TEK receptor tyrosine kinase ( TEK , also known as TIE2 ) genes in the angiogenesis pathway have been identified as candidate genes for nAMD in Chinese,55–57 so were the CETP and Adenosine triphosphate binding cassette subfamily G member 1 ( ABCG1 ) genes in the high-density lipoprotein metabolic pathway 58. By sequencing analysis of PGF , a novel 18-base-pair deletion mutation in the promoter was found to confer over 5-fold of risk to nAMD 59.…”
Section: Molecular Genetics Of Specific Retinal Diseasesmentioning
confidence: 99%
“…In Chinese cohorts from different regions of China, SNPs in CFH and ARMS2 - HTRA1 have also been associated with PCV. In Hong Kong Chinese, ARMS2 rs10490924, HTRA1 rs11200638, CFH rs800292, and CETP rs3764261 were associated with PCV,58,63 and ABCG1 rs225396, ANGPT2 rs13269021, and TIE2 rs625767 were first identified as genetic factors for PCV 56,57,64. In a systematic review and meta-analysis, 31 polymorphisms in 10 AMD-associated genes/loci: ARMS2 , HTRA1 , CFH , C2 , CFB , RDBP , SKIV2L , CETP , 8p21 , and 4q12 , were confirmed to be associated with PCV.…”
Section: Molecular Genetics Of Specific Retinal Diseasesmentioning
confidence: 99%